2018
DOI: 10.7717/peerj.5278
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age on the identification of emotions in facial expressions: a meta-analysis

Abstract: BackgroundEmotion identification is a fundamental component of social cognition. Although it is well established that a general cognitive decline occurs with advancing age, the effects of age on emotion identification is still unclear. A meta-analysis by Ruffman and colleagues (2008) explored this issue, but much research has been published since then, reporting inconsistent findings.MethodsTo examine age differences in the identification of facial expressions of emotion, we conducted a meta-analysis of 24 emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
83
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 70 publications
9
83
2
6
Order By: Relevance
“…The worse performance of older adults in the remaining conditions is in accordance with previous findings. For instance, two metaanalyses showed that an age-related decline in emotional recognition is the predominant pattern across all emotions, with increased difficulties for anger, fear, and sadness (Gonçalves et al, 2018a;Ruffman, Henry, Livingstone, & Phillips, 2008). Middle-aged adults also outperformed older adults, but in fewer conditions than younger adults did.…”
Section: Discussionmentioning
confidence: 99%
“…The worse performance of older adults in the remaining conditions is in accordance with previous findings. For instance, two metaanalyses showed that an age-related decline in emotional recognition is the predominant pattern across all emotions, with increased difficulties for anger, fear, and sadness (Gonçalves et al, 2018a;Ruffman, Henry, Livingstone, & Phillips, 2008). Middle-aged adults also outperformed older adults, but in fewer conditions than younger adults did.…”
Section: Discussionmentioning
confidence: 99%
“…A decline in emotion recognition abilities with advancing age has been welldocumented. Following early descriptions of deficits (e.g., Calder et al, 2003;Malatesta, Izard, Culver, & Nicolich, 1987), a substantial body of research now suggests that older adults experience difficulties recognising emotional states from facial, bodily and vocal stimuli, as well as integrating emotional signals across multiple domains (e.g., Ruffman, Henry, Livingstone, & Phillips, 2008;Gonçalves et al, 2018). Although it is still debated as to whether difficulties extend across all emotional categories (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Outras evidências sugerem que a diferença entre homens e mulheres, poderiam ter uma base neural, uma vez que para cada sexo, áreas diferentes são ativadas durante o REFE e tais diferenças poderiam refletir em diferentes estratégias utilizadas para avaliar as emoções (CAHIL, 2006;SCHULTE-RÜTHER et al, 2008 apud WINGENBACH;ASHWIN;BROSNAN, 2018). Por exemplo, em revisão realizada por Whittle et al (2011) Apesar do aumento no interesse pelo estudo da cognição social e emoção nos últimos anos, ainda não é claro os efeitos do envelhecimento nessas variáveis (KEIGHTLEY et al, 2006;GONÇALVES et al, 2018). Embora seja possível encontrar estudos que avaliaram a associação entre a idade e o REFE (SULLIVAN; RUFFMAN, 2004, ISSACOWITZ et al, 2007, Issacowitz et al (2007) Outros estudos também evidenciaram declínios e/ou pior desempenho no REFE, relacionados à idade (CALDER et al, 2003;WILLIAMS et al, 2006;ISAACOWITZ et al, 2007;LIVINGSTONE;PHILLIPS, 2008;SZE et al, 2012;WEST et al, 2012).…”
Section: Discussionunclassified
“…No estudo de Kaszniak e Menchola (2012), essas emoções também foram percebidas com maior precisão pelos idosos. Tais achados não foram replicados no presente estudo, nem nos estudos de metanálise de Ruffman et al (2008) e Gonçalves et al (2018).…”
Section: Discussionunclassified
See 1 more Smart Citation